Effect of varying doses of tamoxifen on ovarian histopathology, serum VEGF, and endothelin 1 levels in ovarian hyperstimulation syndrome: an experimental study - Pala, Sehmus; Atilgan, Remzi; Ozkan, Zehra Sema; Kavak, Salih Burcin; Ilhan, Nevin; Akpolat, Nusret; Sapmaz, Ekrem (Dove Medical Press Ltd, 2015)
Objective: To examine the effects of low-to-high doses of tamoxifen on ovarian histopathology, serum VEGF, and endothelin 1 levels in ovarian hyperstimulation syndrome (OHSS) in an experimental setting. Materials and methods: A total of 20 female Wistar albino rats, 22 days of age, were randomly divided into four groups. Follicle-stimulating hormone 10 IU was administered subcutaneously in 15 rats on 4 consecutive days, with OHSS induction on day 5 by 30 IU of human chorionic gonadotropin. Group 1 (n=5) comprised 35-day-old control rats, group 2 (n=5) 35-day-old OHSS rats, group 3 (n=5) 27-day-old OHSS rats receiving 1 mg/kg of oral tamoxifen for 7 days, group 4 (n=5) 27-day-old OHSS rats receiving 3 mg/kg of oral tamoxifen for 7 days. All rats were decapitated on day 35. Serum VEGF, endothelin 1, and ovarian follicular reserve were assessed in all rats. Kruskal-Wallis variance analysis and the Mann-Whitney U-test were used for statistical comparisons. A Bonferroni correction was performed to control the inflation of significance, with a significance level set at a P-value of less than 0.025. Results: Despite higher serum VEGF, endothelin 1, follicular reserve, and angiogenesis and fibrosis of the corpus luteum in the OHSS group compared to controls, these differences were not significant (P>0.025, Mann-Whitney U-test). There was a significant reduction in the ovarian follicular reserve in tamoxifen groups compared to controls (P<0.025, Mann-Whitney U-test), while angiogenesis of the corpus luteum, number of atretic follicles, fibrosis, and serum VEGF were significantly higher in rats receiving tamoxifen (P<0.025, Mann-Whitney U-test). Also, significantly lower follicular reserve and fibrosis were observed among rats in the low-dose tamoxifen group in comparison with rats in the high-dose tamoxifen group (P<0.025, Mann-Whitney U-test). No groups had a significant change in endothelin 1 levels (P>0.025, Mann-Whitney U-test). Conclusion: Tamoxifen 1 g and 3 g resulted in a dose-dependent increase in VEGF and endothelin 1 levels, and ovarian follicle reserves were significantly reduced in our experimental model.
Keywords: low-to-high doses of tamoxifen; OHSS; cystic enlargement of the ovaries; hCG